Initial experience with hybrid argon plasma coagulation as a novel local treatment method for tracheobronchial mucoepidermoid carcinoma - Zheng, Xiaoxuan; Herth, Felix; Sun, Jiayuan (Respiration, 2019)
Tracheobronchial mucoepidermoid carcinoma (MEC) is a type of salivary gland tumor. Surgical resection is the main treatment for MEC, but it is associated with risks. Hybrid argon plasma coagulation (HybridAPC®) is an innovative technique combining APC with a water cushion function which can be used for the treatment of MEC. We aimed to evaluate the efficacy and safety of HybridAPC for MEC in 2 patients diagnosed with MEC based on histological examination of biopsies. Full preoperative assessments were done by white-light bronchoscopy, autofluorescence imaging, narrow-band imaging, and radial probe endobronchial ultrasound. HybridAPC was administered after these evaluations. Both patients were followed up for more than 3 months. HybridAPC ablation was completed successfully, with no complications. HybridAPC thus appears to be a safe and efficient treatment for MEC.